Surface ozone in the industrial city of Chelyabinsk, Russia - Tatyana G. Krupnova; Olga V. Rakova; Valeria I. Simakhina; Ekaterina A. Vykhodtseva; Valeriy M. Kochegorov (Russian Geographical Society, 2025)
This work studies the variations in daily and seasonal concentrations of surface ozone (O3), and nitrogen oxides (NO and NO 2) as its precursors in Chelyabinsk, a large industrial city in Russia. A monitoring station located outside the zone of influence of large industrial and transport local sources of air pollution was chosen for the research. The research was carried out during 2019, which can also be considered as a “background” period, because in 2020, during the COVID-19 lockdown, there was a decrease in concentrations of precursors. However, in 2022–2024 concentrations of precursors increased due to increased production capacity. Daily O3 variations are characterized by three peaks that correlate with changes in concentrations of nitrogen oxides (NOx) determined by peak loads and emission intensity of thermal power stations. There are two seasonal peaks of surface O3 concentrations. The spring peak in March is caused by natural processes. In March 2019, an advection of an air mass with different properties and gas composition was observed from areas with powerful sources of precursor gases or saturated with O3 from the south (areas in Kazakhstan). During episodes of high O3 levels, Chelyabinsk was located on the crest of a cyclone, in the warm sector, where low-level jets formed. The summer maximum of surface O3 in June was caused by photochemical reactions during anticyclones and prolonged inversions.